Linear distribution of nematodes in the gastrointestinal tract of tracer lambs - Makovcová, Katerina; Langrová, Iva; Vadlejch, Jaroslav; Jankovská, Ivana; Lytvynets, Andriy; Borkovcová, Marie (Parasitology research, 2008)
Forty-eight tracer lambs were killed in 2004-2007. The abomasum, duodenum, small intestine (jejunum and ileum), colon and caecum were collected and processed for parasites enumeration and identification-mucosal scrapings of both abomasums and intestines were digested. Out of 48 gastrointestinal tracts examined, all were found to be positive for nematode infection. Seventeen species of gastrointestinal nematodes were recovered: Bunostomum trigonocephalum, Cooperia curticei, Haemonchus contortus, Chabertia ovina, Nematodirus battus, Nematodirus filicollis, Oesophagostomum venulosum, Teladorsagia circumcincta, Trichostrongylus axei, Trichostrongylus colubriformis, Trichostrongylus vitrinus, Strongyloides papillosus, Trichuris ovis, Trichuris globulosa, Trichuris skrjabini and Skrjabinema ovis. All species were searched for in the entire gastrointestinal tract. Six species of nematodes were recovered from abnormal sites, naturally in small numbers of lambs as well as in small amounts: Nematodirus battus in the abomasums (6.67% of lambs), N. filicollis in the caecum and in the colon (%4 and 8%, respectively), T. axei in the colon (9.52%), T. colubriformis in the colon (13.89%), T. vitrinus in the caecum (16.67%), in the colon (20.00%) and in the abomasum (3.33%). T. ovis was found in one case in the small intestine.
Keywords: gastrointestinální trakt; Nematode Infections; nemoci ovcí; Strongylida Infections; ovce; infekce hlísticemi řádu Strongylida; Česká republika; Gastrointestinal Tract; Strongylida; nematodózy; Czech Republic; Sheep Diseases; parazitární nemoci střev; Nematoda; zvířata; hlístice; Sheep; Intestinal Diseases, Parasitic; Animals